Electronic imaging impact on image and report turnaround times...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Mattern CWT; King BF Jr.; Hangiandreou NJ; Swenson A; Jorgenson LL; Webbles WE; Okrzynski TW; Erickson BJ; Williamson B Jr.; Forbes GS (Journal of Digital Imaging)
We prospectively compared image and report delivery times in our Urgent Care Center (UCC) during a film-based practice (1995) and after complete implementation of an electronic imaging practice in 1997. Before switching to a totally electronic and filmless practice, multiple time periods were consistently measured during a 1-week period in May 1995 and then again in a similar week in May 1997 after implementation of electronic imaging. All practice patterns were the same except for a film-based practice in 1995 versus a filmless practice in 1997. The following times were measured: (1) waiting room time, (2) technologist's time of examination, (3) time to quality control, (4) radiology interpretation times, (5) radiology image and report delivery time, (6) total radiology turn-around time, (7) time to room the patient back in the UCC, and (8) time until the ordering physician views the film. Waiting room time was longer in 1997 (average time, 26:47) versus 1995 (average time, 15:54). The technologist's examination completion time was approximately the same (1995 average time, 06:12; 1997 average time, 05:41). There was also a slight increase in the time of the technologist's electronic verification or quality control in 1997 (average time, 7:17) versus the film-based practice in 1995 (average time, 2:35). However, radiology interpretation times dramatically improved (average time, 49:38 in 1995 versus average time 13:50 in 1997). There was also a decrease in image delivery times to the clinicians in 1997 (median, 53 minutes) versus the film based practice of 1995 (1 hour and 40 minutes). Reports were available with the images immediately upon completion by the radiologist in 1997, compared with a median time of 27 minutes in 1995. Importantly, patients were roomed back into the UCC examination rooms faster after the radiologic procedure in 1997 (average time, 13:36) than they were in 1995 (29:38). Finally, the ordering physicians viewed the diagnostic images and reports in dramatically less time in 1997 (median, 26 minutes) versus 1995 (median, 1 hour and 5 minutes). In conclusion, a filmless electronic imaging practice within our UCC greatly improved radiology image and report delivery times, as well as improved clinical efficiency. Copyright (c) 1999 by W.B. Saunders Company